Organizing risk: organization and management theory for the risk society - Hardy, Cynthia (2020)
Risk has become a crucial part of organizing, affecting a wide range of organizations in all sectors. We identify, review and integrate diverse literatures relevant to organizing risk, building on an existing framework that describes how risk is organized in three ‘modes’ – prospectively, in real-time, and retrospectively. We then identify three critical issues in the existing literature: its fragmented nature; its neglect of the tensions associated with each of the modes; and its tendency to assume that the meaning of an object in relation to risk is singular and stable. We provide a series of new insights with regard to each of these issues. First, we develop the concept of a risk cycle that shows how organizations engage with all three modes and transition between them over time. Second, we explain why the tensions have been largely ignored and show how studies using a risk work perspective can provide further insights into them. Third, we develop the concept of risk translation to highlight the ways in the meanings of risks can be transformed and to identify the political consequences of such translations. We conclude the paper with a research agenda to elaborate these insights and ideas further